Romantisme Mahasiswa KKN: Pengabdian dan Asimilasi - Jamali, Yusra (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2021)
The Implementation of Real Work Lecture (KKN) is one of the subjects that must be taken by every student with a weight of 6 Semester Credit Units. The implementation of KKN activities in 2019 will be carried out simultaneously with the Educational Field Experience Practices program (PPLK), for students from the Faculty of Tarbiyah, facilitated by the Institute for Research and Community Services (LP2M). KKN participants in the village of Zed, Mendo Barat District, Bangka Regency, amounted to 18 people consisting of 8 students of Islamic Religious Education (PAI) Study Programs, 8 students of Early Childhood Islamic Education Study Program (PIAUD), and 1 person Tadris English Language Study Program (TBI). Implementation of activities that can be carried out by KKN participants for two full months 1) Tutoring (Bimbel) for school residents. 2) Yasinan for housewives and youth of the mosque, which is centered at Al Amin Mosque. 3) Reading huts for ordinary people. 4) Coloring contest for school children, 5) Making corn pillars as a sign that IAIN students have been present in the village. 6) Islamic Hasiri (New Year Hijriyah) Celebration Celebrations. KKN participants received a very respectable place among Zed Village residents. Zed Village is stated to have been very developed, with a very adequate educational background and citizen knowledge. this a condition can support and facilitate KKN participants to socialize in order to help improve the lives of the people of Zed Village. Pelaksanaan Kuliah Kerja Nyata (KKN) merupakan salah satu mata kuliah yang wajib diambil oleh setiap mahasiswa dengan bobot 6 Satuan Kredit Semester. Pelaksanaan kegiatan KKN tahun 2019 dilakukan secara bersamaan dengan program Praktik Pengalaman Lapangan Kependidikan (PPLK), bagi mahasiswa dari Fakultas Tarbiyah, yang difasilitasi oleh Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M). Peserta KKN di desa Zed, Kecamatan Mendo Barat, Kabupaten Bangka, berjumlah 18 orang terdiri dari mahasiswa 8 orang mahasiswa Program Studi (Prodi) Pendidikan Agama Islam (PAI), 8 orang mahasiswa Prodi Pendidikan Islam Anak Usia Dini (PIAUD), dan 1 orang Mahasiswa Prodi Tadris Bahasa Inggris (TBI). Pelaksanaan kegiatan yang dapat dilakukan oleh peserta KKN selama dua bulan penuh 1) Bimbingan Belajar (Bimbel) bagi warga sekolah. 2) Yasinan bagi ibu-ibu rumah tangga dan Remaja masjid yang dipusatkan di Mesjid Al Amin. 3) Pondok Baca bagi masyarakat awam. 4) Lomba mewarnai bagi anak-anak sekolah, 5) Pembuatan tugu jagung sebagai tanda bahwa mahasiswa IAIN pernah hadir di Desa tersebut. 6) Lomba-lomba Perayaan Hasi Besar Islam (Tahun Baru Hijriyah). Peserta KKN mendapat tempat yang sangat terhormat di kalangan warga Desa Zed. Desa Zed dinyatakan sudah sangat berkembang, dengan latar belakang pendidikan dan pengetahuan warga yang sangat memadai. Kondisi ini dapat mendukung dan memudahkan peserta KKN untuk bersosialisasi dalam rangka membantu peningkatan taraf hidup masyarakat Desa Zed.